Hubungan Karakteristik Petani dengan Jasa Pelayanan dan Efektivitas Komunikasi Klinik Agribisnis di Prima Tani Leuwi Sadeng Kabupaten Bogor - N. Rachmawati; A. Saleh (Jurnal Komunikasi Pembangunan, 2009)
The objectives of research are: (1) to know about the communication process in Agribusiness Clinic’s service, (2) toanalyze the level of Agribusiness Clinic communication effectiveness, (3) to analyze relationship between farmer’scharacteristics with communication process in Agribusiness Clinic’s service and (4) to analyze relationship betweenfarmer’s characteristics and communication process in Agribusiness Clinic’s service with Agribusiness Clinic andcommunication effectiveness. This research designed as the description correlation and analyzed by rank Spearmanstatistical test. The research results showed: (1) the communication process in Agribusiness Clinic’s service consistof consultancy/service, discussion, technical construction, printed media and location in farmer’s good perception,(2) communication in Agribusiness Clinic is effective because can be transmission relevant information andsatisfying of member, (3) some individual characteristics have a significant and high significant correlation witheffectiveness of communication are: formal education, level of cosmopolite and non formal education except agenegatively, (4) the formal education has a significant correlation with level of transmission relevant information, thenon formal education and level of cosmopolite has a high significant correlation with satisfying of member, exceptage negatively with Agribusiness communication effectiveness. Agribusiness Clinic’s Service is in good category onlyon printed media have a significant correlation with level of transmission relevant information and high significantcorrelation with satisfying of member, while the location has a high significant only with satisfying of member. Basedon the results of the research that communication with printed media is better than interpersonal communication atPrima Tani in Leuwi Sadeng Sub district, Bogor.